The construction of number in concrete and electronic games: the Kalah game case - de Cássia Gonçalves, Érica [UNESP]; Saravali, Eliane Giachetto [UNESP]; de Sousa, Lilian Pacchioni Pereira [UNESP]; Bessa, Sônia (FapUNIFESP (SciELO), 2024)
Games have sparked interest as an object of study in multiple areas of knowledge. In this research, we will discuss the impacts of the new formats and configurations of games in current times, based on the Piagetian interactionist theory’s contributions. The main objective of the study was to analyze the effects of an intervention with the Kalah game, in its concrete version and in its electronic version, for the construction of the notion of number. Thirty-eight children took part in the investigation, their ages ranged from seven to ten years old, from both genders, enrolled at two county Elementary Schools, located in a small town in the state of Minas Gerais, Brazil, subdivided into 3 groups: EG1- Experimental Group, subjected to the intervention with Kalah in its electronic version; EG2 – Experimental Group, subjected to the intervention with Kalah in its concrete version and CG-Control Group. As instruments of pretest and posttest, the operatory tests/proofs of conservation, classification, and serialization were utilized, to verify if there were qualitative and/or quantitative changes to the thought’s structures. The results indicated the most expressive differences in the assessed structures amongst the subjects from the Experimental Groups when compared to the Control Group, just as there was a distinction in the performances of the subjects from the experimental groups, after the intervention. During the sessions with the Kalah electronic game, it was found that the fundamental principles of the Piagetian theory could not be assured, possibly being one of the pedagogic interventions’ limitations.
A construção do número em jogos concretos e eletrônicos: o caso do jogo Kalah
Keywords: Concrete Games; Electronic Games; Genetic Epistemology; Number notion